THE CONCEPTUAL FRAMEWORK FOR LEARNING ARABIC VOCABULARY THROUGH EDUCATIONAL DIGITAL GAME - Mohammad Taufiq Abdul Ghani; Mahizer Hamzah; Wan Ab Aziz Wan Daud; Saipolbarin Ramli (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
An effective teacher knows the form of technology that can be used in the classroom to help improve their students’ learning. They know what the best tools are, and how and when to use them. Digital game-based learning is a recommended approach which transforms the process of teaching and learning to be more interesting, effective and fun. It has the ability to encourage learners to embrace the challenges and not afraid of failure, create cooperative learning, develop personal responsibility and motivation to succeed. Therefore, this paper attempts to propose an instructional model to develop an educational mobile game application. In order to differentiate between edutainment and entertainment, the educational element must be integrated during the development of the educational game, hence, this paper describes the important requirement for developing the educational mobile game application for a course. This paper briefly describes the proposed model which consists of three parts; input, process, and output. The concept and model proposed may be significant for both instructional designers, program designers, and language practitioners. This paper provided a way of designing an effective digital game which integrated educational elements to improve students’ achievement and performance.